Overview of Mother’s Diet and Behavior on Nutritional Status in Fisher Families in Regemuk Village, Pantai Labu District, Deli Serdang - Sunnii Irtiyah Harahap; Nabila Azzuhra; Nurhidayah Silangit; Nadya Ulfa Tanjung (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2024)
The aim of this study is to describe the eating patterns and behaviors of mothers in relation to the nutritional status of fishermen’s families in Rugemuk Village. This research is a quantitative study with a descriptive design. The sampling technique used in this study is simple random sampling. The results of the study indicate that the percentage of toddlers with incomplete immunization status is still higher than those with complete immunization status. This is one of the reasons why mothers may not be able to monitor their children’s growth and development effectively. The study also found that there are still many toddlers with poor nutritional status compared to those with normal nutritional status.